Acute Respiratory Distress Syndrome Induced by a Swine 2009 H1N1 Variant in Mice - Zhang, Yi; Sun, Honglei; Fan, Lihong; Ma, Yuan; Sun, Yipeng; Pu, Juan; Yang, Jun; Qiao, Jian; Ma, Guangpeng; Liu, Jinhua (PLOS ONE, 2012)
Background Acute respiratory distress syndrome (ARDS) induced by pandemic 2009 H1N1 influenza virus has been widely reported and was considered the main cause of death in critically ill patients with 2009 H1N1 infection. However, no animal model has been developed for ARDS caused by infection with 2009 H1N1 virus. Here, we present a mouse model of ARDS induced by 2009 H1N1 virus. Methodology Principal Findings Mice were inoculated with A/swine/Shandong/731/2009 (SD/09), which was a 2009 H1N1 influenza variant with a G222D mutation in the hemagglutinin. Clinical symptoms were recorded every day. Lung injury was assessed by lung water content and histopathological observation. Arterial blood gas, leukocyte count in the bronchial alveolar lavage fluid and blood, virus titers, and cytokine levels in the lung were measured at various times post-inoculation. Mice infected with SD/09 virus showed typical ARDS symptoms characterized by 60% lethality on days 8–10 post-inoculation, highly edematous lungs, inflammatory cellular infiltration, alveolar and interstitial edema, lung hemorrhage, progressive and severe hypoxemia, and elevated levels of proinflammatory cytokines and chemokines. Conclusions/Significance These results suggested that we successfully established an ARDS mouse model induced by a virulent 2009 H1N1 variant without previous adaptation, which may be of benefit for evaluating the pathogenesis or therapy of human ARDS caused by 2009 H1N1 virus.